"You've been on my mind ever since": A content analysis of expressions of interpersonal attraction in Craigslist.org's Missed Connections posts. (January 2016) - Bevan, Jennifer L.; Galvan, Jimena; Villasenor, Justin; Henkin, Joanna
Abstract: This study examined how interpersonal attraction was described in Craigslist.org's Missed Connections postings via a quantitative content analysis of randomly selected posts in the United States. Results indicated that, as predicted, Missed Connections postings contained a combination of multiple verbal (e.g., spoken interactions that are not greetings or praise/compliments) and nonverbal (e.g., physical attractiveness, eye contact, nonverbal body movements) attraction expressions; these posts included an average of just over two attraction expressions. Physical attractiveness was the most frequently expressed form of interpersonal attraction. There were no biological sex or sexual orientation differences in relation to which and how many attraction expressions were included in Missed Connections posts. Implications for attraction and online personal advertisement research are described. Highlights: Study examines interpersonal attraction in Missed Connections posts. Quantitative content analysis used to code for attraction expressions. Physical attraction is most frequent attraction expression. Missed Connections posts contain two attraction expressions, on average. Attraction expressions do not vary by sex or sexual orientation.